2001
DOI: 10.1177/00912700122010735
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Higher Than Standard Dose of Doxylamine‐Pyridoxine (Diclectin®) for Nausea and Vomiting of Pregnancy

Abstract: A delayed-release combination of doxylamine-pyridoxine (D-P) (Diclectin) is the only approved antiemetic medication for use in pregnancy in Canada. The standard recommended dose is up to 4 tablets a day, regardless of body weight or severity of symptoms. The objective of this study was to determine the incidence of adverse maternal and fetal effects and pregnancy outcome in 225 women taking Diclectin at the recommended (n = 123) or higher than recommended (n = 102) doses. In this observational, prospective stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 1 publication
0
30
0
1
Order By: Relevance
“…No increase in adverse events or adverse pregnancy outcomes for the higher than standard dose of Diclectin ® were observed [75]. …”
Section: Optimal Nvp Treatment Using Diclegis®/diclectin®mentioning
confidence: 99%
See 1 more Smart Citation
“…No increase in adverse events or adverse pregnancy outcomes for the higher than standard dose of Diclectin ® were observed [75]. …”
Section: Optimal Nvp Treatment Using Diclegis®/diclectin®mentioning
confidence: 99%
“…The results showed that higher than standard dose of Diclectin ® , when calculated per kilogram of body weight, did not affect either the incidence of maternal adverse effects or adverse pregnancy outcomes [75]. …”
Section: Fetal Safety Of the Delayed-release Combination Of Doxylaminmentioning
confidence: 99%
“…13 Furthermore, although the standard recommended dose is up to 40 mg (four tablets) a day, a study was conducted comparing 123 pregnant women at recommended standard doses and 102 pregnant women at higher than recommended doses of up to 12 tablets a day. 8 This study revealed that higher than standard doses, up to 12 tablets a day, were found to be more efficacious without significantly increasing the rate of adverse drug reactions, suggesting that there is variability in response among women, and standard doses may not be adequate for all women to manage NVP symptoms effectively. 8…”
Section: Discussionmentioning
confidence: 79%
“…Higher-than-standard doses of DOX/pyridoxine have been studied in pregnancy with some women requiring up to 120 mg (12 tablets) a day with no apparent increased maternal or fetal risks. 8 Clearly, there is variability in the efficacy of DOX/pyridoxine, but the factors underlying this variability are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…En l'absence de signes de gravité, une prise en charge ambulatoire sera alors possible avec des conseils diététiques adaptés (éviter les aliments épicés, boissons abondantes), les signes d'alerte qui doivent amener la patiente à consulter (poursuite de la perte de poids, poursuite des vomissements malgré le traitement), un traitement médical par antiémétiques (métoclopramide, Primpéran ® , trois suppositoires par jour ou doxylamine, Donormyl ® , 1 cp × 2/j) [15,16] et une proposition de prise en charge psychologique en cas de facteurs de risques avérés par l'interrogatoire et si possible avec la psychologue du service afin d'assurer un suivi régulier au cours de l'hospitalisation et tout au long de la grossesse.…”
Section: Proposition De Prise En Chargeunclassified